2014
DOI: 10.1016/j.juro.2014.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes in the Management of Isolated Nodal Recurrences: A Multicenter, International Retrospective Cohort

Abstract: Surgical resection represents the best curative option for patients who present with isolated retroperitoneal lymph node recurrence of renal cell carcinoma. Durable postoperative progression-free survival is attainable in many patients regardless of histology or clinical TNM stage. In addition, our cohort showed a lower renal cell carcinoma related mortality rate than in previous series of local metastasis. As such, all patients free of precluding comorbidities should be considered candidates for complete surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…The paucity of existing data on this cohort probably reflects both the relative infrequency of isolated RPLN recurrence from RCC, as well as clinicians' historical reluctance to consider resection in these cases. To facilitate a more robust assessment (albeit still with a modest sample size), we formed Meanwhile, our present finding of an association between the interval from nephrectomy to the development of RPLN recurrence with outcome after resection is consistent with data from prior series of patients with metastatic RCC [7,12,21,22]. Specifically, we found that RPLN recurrence at ≤12 months of nephrectomy was associated with a significantly increased risk of subsequent progression.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The paucity of existing data on this cohort probably reflects both the relative infrequency of isolated RPLN recurrence from RCC, as well as clinicians' historical reluctance to consider resection in these cases. To facilitate a more robust assessment (albeit still with a modest sample size), we formed Meanwhile, our present finding of an association between the interval from nephrectomy to the development of RPLN recurrence with outcome after resection is consistent with data from prior series of patients with metastatic RCC [7,12,21,22]. Specifically, we found that RPLN recurrence at ≤12 months of nephrectomy was associated with a significantly increased risk of subsequent progression.…”
Section: Discussionsupporting
confidence: 82%
“…These data represent what is to our knowledge the largest series to date reported on this topic, and suggest that in the setting of RPLN recurrence after nephrectomy, surgical resection should be considered for appropriately selected patients. Two prior small (15 patients and 22 patients, respectively) series have described the use of surgical resection for patients with isolated RPLN recurrence after nephrectomy [21,22]. The paucity of existing data on this cohort probably reflects both the relative infrequency of isolated RPLN recurrence from RCC, as well as clinicians' historical reluctance to consider resection in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 46% progressed to metastatic disease with a median progression free survival of 12.7 months. 27 In our series, we report a larger subgroup of patients(41/102 patients) with localized lymph node recurrence undergoing complete surgical excision. The overall median recurrence free survival was 23 months and we noted no significant differences in CSS where we stratified by location of recurrence (renal fossa/soft tissue, lymph node or adrenal) within the retroperitoneum (Figure 2D).…”
Section: Discussionmentioning
confidence: 86%
“…Clear cell renal cell carcinoma (ccRCC) is the most common histologic type in kidney cancers. Overall median progression-free survival (PFS) is 12 months in ccRCC and 17 months in non-clear cell RCCs (2). Although nearly 80% of ccRCC cases are considered to be cured by resection, the median overall survival (OS) for patients with metastatic RCC is less than 3 years (3).…”
Section: Introductionmentioning
confidence: 99%